ANALISIS MOTIVASI KERJA PEGAWAI PADA KANTOR BUPATI KABUPATEN TOLITOLI - Nur’aini, Andi (Katalogis, 2017)
This research was conducted in order to examine and analyze employee motivation At Regent Office Tolitoli, this research used Qualitative Research Methods. Informants of this research is a Civil Servant, among others; Regional Secretary, General Administration Assistant III, Head of the General Government Administration, Head and Head of Organization and Management, Head of Public Welfare, Head of Public and Supplies. The technique used in the field of data collection are observation, interview and documentation. Results of research on Employee Motivation Regent Office Tolitoli, if in the review of Motivation Herzberg there are two factors that both motivators and hygiene can be concluded that to achieve the goals of the organization is still need for improvement of motivation high because of unsatisfactory employee. Salary / wage can be said to be less going well, because there are still some employers who are less sensitive and have a sense of empathy towards their subordinates, especially for permanent employees in providing benefits, incentives or other bonuses.